PERBANDINGAN HASIL BELAJAR STATISTIK DASAR DENGAN METODE PRAKTIKUM - Yeti Nurizzati (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
The Tadris English Department 2015/2016 consists of 4 classes, but only 2 classes (C and D) using the practicum method in Basic Statistics learning. Class C and D Department of Tadris English has different characteristics. Class C is more preferable to class D in learning. This is evident from the level of attendance and liveliness in the classroom. So the alleged that the results of learning will cause a difference. Therefore, this study was conducted to compare differences in learning outcomes Basic Statistics before and after using the practice method in the Department of Tadris English class C and D; as well as comparing the differences in learning outcomes Basic Statistics using the class practice method C and D. Both classes are experimental classes that are independent with the treatment given that the basic statistical learning with the practice method so that it includes the type of quantitative comparational research. Homogeneity test results of two homogeneous class with p_v>α. The result of t test of the correlated sample that derived from the comparison of UTS value with UAS of both classes has increased significantly with the value of p_v